Impact of Foreign Direct Investment (FDI) on Housing Affordability Index: Vector Autoregressive Model - Anderson Chua Chen Lu; Jerome Kueh; Yong Sze Wei; Josephine Yau; Audrey Liwan (Journal of International Business, Economics and Entrepreneurship, 2020)
This paper aims to investigate the short and long term association between Foreign Direct Investment (FDI) and overall consumer affordability in Malaysia Real Estate Sector using Vector Autoregressive model. Sample period used is 2009:Q1 to 2017:Q4. FDI is scapegoated as the leading cause of decreasing affordability in real estate. In most cases, FDI on real estate contributes to the rising income of the country. Increasing income promotes demand to a higher threshold level. Thus, theoretically will cause housing price to increase. Through this study, evidence of no cointegration and absence of Granger causality converge towards deficiency of relationship among FDI and Housing Affordability Index (HAI). Findings pointed out FDI is not the cause of decreasing HAI.